Challenges, opportunities and innovations in public administration in the next decade - Thamrongthanyawong, Sombat (Asian Review of Public Administration, 2011)
This article is developed from the presidential address given in the opening of EROPA 2011, the 23rd General Assembly and conference of the Eastern Regional Organization for Public Administration held in Bangkok, Thailand in February 2012. It reflects on the main components of the conference theme "Challenges, Opportunities and Innovations in Public Administration in the Next Decade". Over the coming decade, the government sector will play an essential role in a broad range of fields, particularly in such times as experienced now. It is during periods such as this when a country faces many challenges that opportunities and innovation must come to the fore. In order to facilitate taking advantage of these challenges and turning them into opportunities, we must enhance the efficiency and effectiveness of public administration. Therefore, consistently with the main EROPA 2011 theme, this article will discuss three major areas: 1) challenges, 2) oppotunities and 3) innovations.